Comparision of antibiotics and antimicrobial alternatives on growth performance of weanling pigs in a commercial environment - Keegan, T.P.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 320 weanling pigs (11.7 lb and 14 ± 3 d of age, PIC) was used to determine the effects of antibiotics and antimicrobial alternatives in diets for nursery pigs reared in a commercial environment. Pigs were fed one of 5 experimental diets: 1) control with no antimicrobials; 2) carbadox (50 g/ton); 3) Lacto- Sacc® (0.2%); 4) Bio-Plus® 2B (0.05%); or 5) Bio-Mos™(0.3%). Lacto Sacc® is a concentrated form of selected live yeast cells while Bio Plus® 2B contains two bacillus strains. Bio-Mos™ is a mannanoligosaccharide derived from yeast. Overall (d 0 to 31 postweaning), pigs fed the control diet or diets containing Bio Mos had greater (P<0.05) ADG compared to pigs fed the diet containing Bio Plus 2B. Pigs fed the diet containing Bio Plus 2B had lower (P<0.05) daily feed intake compared to pigs fed the control diet or diets containing carbadox or Bio Mos with Lacto Sacc being intermediate in performance. There was no difference in feed efficiency among pigs fed various dietary treatments. In conclusion, in this commercial environment, the additions of carbadox or antimicrobial alternatives to the control diet were not effective in improving nursery pig performance.
Keywords: Nursery pig; Antibiotics; Additive; Swine